Tunable S+/S band Q-switched thulium-doped fluoride fiber laser using tungsten ditelluride (WTe2) - Ahmad, H.; Ismail, Nor Najwa; Aidit, S. N.; Yusoff, Norazriena; Zulkifli, Mohd Zamani (Elsevier B.V., 2020)
A tunable, passively Q-switched thulium-doped fluoride fiber laser (TDFFL) using a tungsten ditelluride (WTe2) thin film based saturable absorber (SA) was proposed and its operational efficacy demonstrated. At a maximum pump power of 250 mW, a Q-switched output at 1494 nm with a 3-dB bandwidth of 3 nm was obtained. The repetition rate was measured to be 36.5 kHz with a minimum pulse width of 3.7 µs, as well as a signal-to-noise ratio (SNR) of approximately 42 dB. Utilizing a tunable bandpass filter (TBPF), tunable Q-switching operation was achieved from 1459 to 1513 nm, giving a tuning range of 54 nm. The proposed laser would have significant use for systems operating in the S-band region, particularly for optical communications networks.